KELUARGA DALAM MEMBENTUK KARAKTER ANAK - Anisa Indah Mulyani; Intan Nopriyanti; Ratmelia; Suwandi; Sukatin; Alfi Rochmi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2022)
Children are a gift that cools the eyes and this is a blessing from Allah SWT. Every parent must want a child who is pious, pious and obedient to Allah SWT and parents. Behind the joy of the child, in fact he needs the attention and guidance of parents. Likewise parents, all the best they want to give as a sign of love for the baby, because the baby is priceless. The family is an important factor in the formation of a child's personality. The family is the first and foremost educational forum in the child's life history which is an important basis in the formation of the human character itself. To create a strong character and good spirit in children in the family, it is necessary to create a harmonious and dynamic family atmosphere, this can be created if strong two-way coordination and communication are built between parents and children.